Partisipasi Warga Negara Digital Terhadap Proses Demokrasi Pancasila - Hidayat, Obby Taufik (Antroposen: Journal of Social Studies and Humaniora, 2023)
This article aims to compare nine features of digital citizenship with case studies conducted on digital citizen participation in encouraging a more democratic and accountable government. A case study approach was used in this research through interviews, observations, and documentation studies. Researchers have contributed to developing case study research from various scientific disciplines. This case study research encourages a detailed investigation of the unit of analysis in its context. The results of this study show that digital citizenship education can encourage digital citizen participation in a more accountable and democratic government. Therefore, today's society needs to be trained on the nine elements of digital citizenship to collaborate and cooperate with various parties in ensuring that tensions between digital citizens and the government can find common ground to realize Pancasila Democracy. This study expands the theoretical discourse and practice of developing digital citizen participation towards Pancasila Democracy.